An Aggregation-Induced Emission-Based Indirect Competitive Immunoassay for Fluorescence “Turn-On” Detection of Drug Residues in Foodstuffs - Yu, Wenbo; Li, Ying; Xie, Bing; Ma, Mingfang; Chen, Chaochao; Li, Chenglong; Yu, Xuezhi; Wang, Zhanhui; Wen, Kai; Tang, Ben Zhong; Shen, Jianzhong (Frontiers in Chemistry, 2019)
A new fluorescent “turn-on” probe-based immunosensor for detecting drug residues in foodstuffs was established by combining the mechanism of aggregation-induced emission (AIE) and an indirect competitive enzyme-linked immunosorbent assay (ELISA). In this study, a luminogen, with negligible fluorescence emission (TPE-HPro), aggregated in the presence of H2O2 and exhibited strong yellow emission based on its AIE characteristics. This AIE process was further configured into an immunoassay for analyzing drug residues in foodstuffs. In this approach, glucose oxidase (GOx) was used as an enzyme label for the immunoassay and triggered GOx/glucose-mediated H2O2 generation, which caused oxidation of TPE-HPro and a “turn-on” fluorescence response at 540 nm. To quantitatively analyze the drug residues in foodstuffs, we used amantadine (AMD) as assay model. By combining the AIE-active “turn-on” fluorescent signal generation mechanism with conventional ELISAs, quantifying AMD concentration in chicken muscle samples was realized with an IC50 (50% inhibitory concentration) value of 0.38 ng/mL in buffer and a limit of detection of 0.06 μg/kg in chicken sample. Overall, the conceptual integration of AIE with ELISA represents a potent and sensitive strategy that broadens the applicability of AIE-based fluorometric assays.